2019
DOI: 10.1158/1541-7786.mcr-18-1057
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Prostate Cancer with Associated Gleason Score Using Mass Spectrometry Imaging

Abstract: Diagnosis of prostate cancer is based on histologic evaluation of tumor architecture using a system known as the "Gleason score." This diagnostic paradigm, while the standard of care, is time-consuming, shows intraobserver variability, and provides no information about the altered metabolic pathways, which result in altered tissue architecture. Characterization of the molecular composition of prostate cancer and how it changes with respect to the Gleason score (GS) could enable a more objective and faster diag… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(65 citation statements)
references
References 46 publications
4
61
0
Order By: Relevance
“…Shown in Figure 1A is a representative tumor in which comparison of spectral data from these regions revealed a tumor-specific PL composition that was distinct from that detected in pathologically benign epithelium or a region of high-grade prostatic intraepithelial neoplasia (PIN) from the same patient ( Figure 1B; Supplementary Figure 1A). Distinct PL mass spectra and specific masses (eg m/z 756.53, Figure 1A) were consistently detected in multiple independent tumor regions assessed across 3 individual PCa patients (Supplementary Figure 1B,C), consistent with recent reports (16,17) that characteristic changes in lipid composition accompany prostate tumorigenesis.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Shown in Figure 1A is a representative tumor in which comparison of spectral data from these regions revealed a tumor-specific PL composition that was distinct from that detected in pathologically benign epithelium or a region of high-grade prostatic intraepithelial neoplasia (PIN) from the same patient ( Figure 1B; Supplementary Figure 1A). Distinct PL mass spectra and specific masses (eg m/z 756.53, Figure 1A) were consistently detected in multiple independent tumor regions assessed across 3 individual PCa patients (Supplementary Figure 1B,C), consistent with recent reports (16,17) that characteristic changes in lipid composition accompany prostate tumorigenesis.…”
Section: Resultssupporting
confidence: 86%
“…While panels of circulating plasma lipids have previously been associated with prostate cancer risk (8), diagnosis (9) and patient outcome (10), analysis of the prostate tumor lipidome has largely been confined to cell line-based studies (11)(12)(13), which lack clinical relevance. The recent evidence of malignancy-related changes in lipid composition of prostate tumors provided by mass spectrometry-based imaging studies (14)(15)(16)(17) supports undertaking a more detailed and quantitative study of the clinical prostate cancer lipidome. Moreover, treatment-related changes in the lipidome, which may reveal new resistance-related vulnerabilities, remain completely unexplored.…”
Section: Introductionmentioning
confidence: 91%
“…Taken together, the deep learning data analysis strategy presented here provides the ability to learn the 69 , and 3D MALDI FT-ICR MSI dataset of PDX mouse brain model of glioblastoma 3 . The MSI datasets, without prior peak picking, were exported in the standardized format imzML 49 and converted to HDF5 format 50 for variational autoencoder analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies showed changes in CL content and/or composition in tumor tissues or cancer cells. In human prostate cancer tissues, changes in the quantity of various lipids including CL were observed, and CL content was found to be increased in the regions with high tumor cell density [34]. In addition, a modification of CL composition has been observed in tumor prostate tissue of patients [34].…”
Section: Cardiolipin Metabolismmentioning
confidence: 98%
“…In human prostate cancer tissues, changes in the quantity of various lipids including CL were observed, and CL content was found to be increased in the regions with high tumor cell density [34]. In addition, a modification of CL composition has been observed in tumor prostate tissue of patients [34]. Thus, in tumor tissue, CL composition in palmitoleic acid (C16:1) was increased compared with non-tumor tissue.…”
Section: Cardiolipin Metabolismmentioning
confidence: 99%